Maria Brown on Ten Lessons for a Successful Career - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Ex-BBC journalist and producer Maria Brown has spent over 14 years in the international media industry. She is a cofounder and managing director, acquisitions and programming of the Asian Food Channel (AFC), the region’s first 24-hour pay channel devoted to matters culinaire from across the globe. Brown delivered a talk at the Singapore Management University recently on “Ten lessons to have a successful career” as part of the Wee Kim Wee Centre CEO Talks Series.